Bangladesh : Assessment Letter for the Asian Development Bank. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Assessment Letters or Statements may be prepared for member countries with Fund-supported programs; receiving Fund emergency assistance; with staff-monitored programs; or surveillance-only cases. They are typically produced for use by the country with multilateral or bilateral donors or creditors, in particular the World Bank and other International Financial Institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: IMF Relation; IMF Staffs Assessment; IMF's Executive Board; PP; Bangladesh